Scotopteryx kurmanjiana, a new species from the Kopet-Dagh Mountains (Lepidoptera, Geometridae, Larentiinae) - Hossein Rajaei Sh.; Gyula M. László (Nota Lepidopterologica, 2014)
Scotopteryx kurmanjiana sp. n. is described from the Kopet-Dagh Mountains in Northeast Iran and South Turkmenistan. The new species is considered to be closely related to Scotopteryx kuznetzovi (Wardikian, 1957) described from Armenia. Detailed description of the external morphology and the genitalia characters of the male with six colour photographs and two illustrations of genitalia are provided.